CHEMOTHERAPY OF GASTRO-INTESTINAL NAMATODES IN COMMON PEAFOWL (PAVO CRISTATUS) - M. Ashraf, Faisal Noman Waraich, I.G. Ahmad and K. Pervez (Pakistan Veterinary Journal, 2002)
The present study was undertaken to find out the prevalence of gastro-intestinal nematodes in common peafowl (Pavo cristatus) at Lahore Zoo and to evaluate the comparative efficacy of albendazole, levamisole HCI and oxfendazole. Fifty-two faecal samples of the birds were examined in Medicine Laboratory, College of Veterinary Sciences, Lahore, with direct smear method for the identification of nematode ova. Forty two samples out of 52 were found positive (80.77%) for single or mixed infection of Capillaria spp., Ascaridia galliand Heterakis gallinae, and the individual percentages being 59.62, 38.46 and 13.46 respectively. Out of 42 infected birds 40 were chosen for medication and divided into four groups, each consisting of 10 birds (A= treated with albendazole, B=treated with levamisole, C = treated with oxfendazole and group D= untreated control). Faecal samples of experimental birds were examined for counting of eggs per gram of faeces on day '0' (pre-medication). Faecal egg counts were again carried out on day 5 and 10 post-medication and percentage reduction of EPG was calculated. Oxfendazole was found to be the most effective (98.88%) among the three anthelmintics, followed by levamisole (97.3%) and albendazole (95.60%).